A systematic review and meta-analysis of health-related quality of life among patients with cardiovascular diseases in Ethiopia - Tassew, Worku Chekol; Zeleke, Agerie Mengistie; Woldie, Samson Sisay; Ferede, Yeshiwas Ayale (Frontiers in Cardiovascular Medicine, 2024)
IntroductionDespite Ethiopia's best efforts, the physical, psychological, social, and environmental aspects of quality of life among patients with cardiovascular illnesses such as hypertension have not received adequate consideration. The quality of life among patients with cardiovascular diseases in Ethiopia has not been thoroughly examined; therefore, this study aimed to assess the prevalence and factors associated with health-related quality of life among patients with cardiovascular diseases.MethodsThe results of this systematic review and meta-analysis were reported in accordance with the International Recommended Reporting items for Systematic Review and Meta-analysis guidelines. A thorough search of published literature was conducted utilizing reliable databases (PubMed) and web-based search platforms (Science Direct, African Journals Online, and Google Scholar). The extracted data were imported to STATA version 11 to determine the pooled prevalence of health-related quality of life. The heterogeneity among the results of the primary studies was analyzed using Cochran's Q test and quantified using I2 statistics. A funnel plot and Egger's test were used to determine the presence of publication bias.ResultsThis systematic review and meta-analysis included 10 published articles. The pooled prevalence of health-related quality of life among patients with cardiovascular diseases in Ethiopia was 45.32% [95% confidence interval (CI): 37.44–53.20, P < 0.001]. Age older than 60 years [odds ratio (OR) = 3.71, 95% CI: 2.81–4.89], presence of chronic comorbidities (OR: 2.87, 95% CI: 1.72–3.4.79), and rural residence (OR = 15.31, 95% CI: 2.82–83.26) were associated with poor health-related quality of life.ConclusionAccording to the findings of this study, a large number of patients with cardiovascular diseases in Ethiopia experience poor health-related quality of life. Furthermore, age above 60 years, presence of comorbidities, and rural residence were found to have substantial impacts on the quality of life of patients. As a result, this review recommends that quality-of-life evaluation be included in routine patient treatment regimens.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?RecordID=573993, identifier (CRD42024573993).